Diagnostic imaging appearance of canine gastric leiomyomas: Four cases. Issue 3 (23rd April 2022) - Segarra, Amaya; Herrtage, Michael E.; Salgüero, Raquel
Abstract: Gastric leiomyoma (GL) is an uncommon benign neoplasm found in older dogs and generally identified as an incidental finding. The purpose of this paper is to describe the imaging appearance of GL in different diagnostic imaging modalities (radiography [XR], ultrasonography [US] and computed tomography [CT]). All three modalities revealed a mass arising within the gastric wall, radiopaque on XR, hypoechoic on US and isoattenuating on CT, with intralesional radiopaque/hyperechoic/hyperattenuating foci, respectively. US and CT are sensitive and proved very useful in the diagnosis of this type of neoplasia, identifying the location, extent and appearance of the mass before a surgical treatment. GL should be considered as a possible diagnosis in the presence of dystrophic mineralisation within a gastric mass.